Dietary creatine-guanidinoacetate acutely improves circulating creatine levels and running performance in healthy men and women: Creatine-guanidinoacetate for creatine status and exercise performance - Andjelic, Bogdan; Todorovic, Nikola; Vranes, Milan; Ostojic, Sergej (Progress in Nutrition, 2024)
N/A